FORMULATION AND EVALUATION OF METFORMIN HCL RELEASE FROM TOPICAL PREPARATION USING TWO DIFFERENT TYPES OF MEMBRANE - KHAN, SANDAL; JAN, SYED UMER; GUL, RAHMAN; QADIR, MIR ABDUL; SHAH, KIFAYAT ULLAH (International Journal of Current Pharmaceutical Research, 2020)
Objective: Present study was carried to formulate and evaluate the transdermal ointment containing the metformin HCl active ingredient and to assess their Physicochemical studies. Methods: Metformin HCl ointment was prepared with various thymol oil concentrations. Ointments were assessed with different characterizations; Physical appearance, viscosity, pH, drug content, Consistency, homogeneity, consistency. Differential scanning calorimetry analysis, XRD studies. It was used in vitro via using Franz cells along with the use of two membranes i.e. Nylon and cellulose membrane. Results: SEM and XRD studies showed that there were no physical and chemical interactions between excipients and drug. All the formulations showed good physicochemical characteristics. The formulation showed different releases. It was observed that nylon had better release properties as compared to cellulose. Conclusion: In the study conducted here, it was observed that Nylon membrane showed better discriminating power to compare among the formulation. This indicates that it has gotten prime importance to watch the effect of the membrane upon the release pattern of the various formulations. In order to improve the formulation, we can use in vitro diffusion cell experiments of transdermal drug delivery.